2017
DOI: 10.1116/1.4984010
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of poly(methylmethacrylate): Effects on fluorescence immunoassay

Abstract: The authors present surface engineering modifications through chemistry of poly(methylmethacrylate) (PMMA) that have dramatic effects on the result of surface-bound fluorescence immunoassays, both for specific and nonspecific signals. The authors deduce the most important effect to be clustering of antibodies on the surface leading to significant self-quenching. Secondary effects are attributable to the formation of sparse multilayers of antibody. The authors compare PMMA as an antibody support surface with ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…nSLD values for the PMMA and PEG layers were calculated from the bulk densities of the molecules and were fixed during fitting at the calculated values. Recent studies of PMMA and PMMA–PEG thin films have shown that the nSLD values used are appropriate and characterize the layers well. Since the chemical composition of APTES layers can vary because of variations in the extent of hydrolysis during deposition reactions, the nSLD of APTES layers was not fixed during data fitting.…”
Section: Methodsmentioning
confidence: 99%
“…nSLD values for the PMMA and PEG layers were calculated from the bulk densities of the molecules and were fixed during fitting at the calculated values. Recent studies of PMMA and PMMA–PEG thin films have shown that the nSLD values used are appropriate and characterize the layers well. Since the chemical composition of APTES layers can vary because of variations in the extent of hydrolysis during deposition reactions, the nSLD of APTES layers was not fixed during data fitting.…”
Section: Methodsmentioning
confidence: 99%
“…13 Also, there are examples in plastics such as PDMS or PMMA. 14,15 The general approach is the chemical modification of these supports using dendrons to control surface wettability, probe spacing, or improve bioreactivity. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…13 Also, there are examples in plastics such as PDMS or PMMA. 14,15 The general approach is the chemical modification of these supports using dendrons to control surface wettability, probe spacing, or improve bioreactivity. [16][17][18] A novelty of our study is the dendron-mediated immobilization strategy for developing a forest-array DNA biosensor onto a polycarbonate chip through the focal point.…”
Section: Introductionmentioning
confidence: 99%
“…Pese a que la inmovilización de dichos polímeros fractales sobre superficies sólidas, planas y convencionales (sílice, oro y mica) ha sido descrita , actualmente se están investigando otras superficies novedosas. En concreto, se han desarrollado superficies dendronizadas sobre poliéster (Morshed et al, 2019), celulosa (Vidal et al, 2020, metacrilato (Evans et al, 2021), fibra óptica (Kamil et al, 2019) y polímeros orgánicos como PS o PMMA (Bosnjakovic et al, 2012), (Akers et al, 2017). En concreto, el grupo de Cao y colaboradores fue pionero en anclar dendrímeros PAMAM-COOH en superficies termoplásticas híbridas de PDMS y SU-8 (Qin et al, 2015) para la detección de células de E.Coli (Jiang et al, 2017), (Hao et al, 2019) y células tumorales CRM-CEM (Qin et al, 2017).…”
Section: Chips Con Estructuras Tridimensionalesunclassified
“…Concretely, dendrons are monomers of dendrimers and can be covalent bonded through the focal point and by the hiperbranched peripheral groups (Kawauchi, 2015) onto solid surfaces. Those dendronized surfaces has been constructed in conventional surfaces such as gold and glass , just a minority of authors have developed integrated plataforms with polymeric surfaces in PDMS or PMMA ) (Akers, 2017), here, we develop a forest-array biosensor onto polycarbonate chip. For that purpose, DNA-dendron conjugates were photochemically bounded by smart click chemistry and immobilized in activated polymer.…”
Section: Introductionmentioning
confidence: 99%